2019
DOI: 10.1124/jpet.119.256750
|View full text |Cite
|
Sign up to set email alerts
|

Microneedles Coated with Tramadol Exhibit Antinociceptive Effect in a Rat Model of Temporomandibular Hypernociception

Abstract: Coated microneedles have emerged as a promising drug delivery system for inflammatory pain treatment. We have previously shown that tramadol injection into the rat temporomandibular joint (TMJ) induces an antinociceptive and anti-inflammatory effect. In this study, microneedles coated with tramadol were investigated as a platform to treat TMJ pain. Male Wistar rats were administered tramadol using an intra-TMJ injection or with microneedles coated with tramadol, followed by 1.5% formalin nociceptive challenge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Likewise, Jain et al (2016) found that although the amount of 5aminolevulinic acid on a microneedle patch increased from 206-350 to 458-680 mg/patch, the delivery efficiency was found to have fallen from about 90% to 60% across the dose range. Abdalla et al (2019) also found a similar threshold effect. When they coated tramadol onto microneedles, they saw that at 20% or 30% (w/v) of tramadol in the coating solution, the resulting delivery efficiencies were similar and measured at 73% and 72%, translating into delivery of 139 and 185 mg tramadol, respectively.…”
Section: Delivery Efficiencymentioning
confidence: 56%
See 1 more Smart Citation
“…Likewise, Jain et al (2016) found that although the amount of 5aminolevulinic acid on a microneedle patch increased from 206-350 to 458-680 mg/patch, the delivery efficiency was found to have fallen from about 90% to 60% across the dose range. Abdalla et al (2019) also found a similar threshold effect. When they coated tramadol onto microneedles, they saw that at 20% or 30% (w/v) of tramadol in the coating solution, the resulting delivery efficiencies were similar and measured at 73% and 72%, translating into delivery of 139 and 185 mg tramadol, respectively.…”
Section: Delivery Efficiencymentioning
confidence: 56%
“…Mass of material coated on microneedles. It has been observed that as the amount of material coated is increased, then after a certain threshold amount, the delivery efficiency decreases (Widera et al, 2006;Kim et al, 2014;Jain et al, 2016;Abdalla et al, 2019). In a study done by Widera et al (2006) it was seen that the delivery efficiency in hairless guinea pig skin using microneedles coated with radiolabeled ovalbumin was a function of the amount coated.…”
Section: Delivery Efficiencymentioning
confidence: 99%
“…In addition, intra-articular injection of tramadol significantly reduced the levels of the proinflammatory cytokines TNF-α and IL-1b. However, after 2 hours, the levels of TNF-α, IL-1b, and IL-10 were not significantly different from those of the nontreated group, indicating that the anti-inflammatory effect produced by intra-articular tramadol injection was of short duration, but after treatment with coated MNs, the levels of TNF-α and IL-1b were reduced and the levels of IL-10 were increased for up to 6 days 76 and the pain were controlled for a long period of time. This study shows that coated MNs have great potential for use in the treatment of pain in arthritis.…”
Section: Coated Mnsmentioning
confidence: 77%
“…Therefore, 15d-PGJ 2 cream associated with MNs is a promising patient-friendly therapeutic method for pain management related to TMJOA. Similarly, another study coats MNs with tramadol, and finds that tramadol delivery via MNs produce more durable antinociceptive effects than intra-TMJ injection of tramadol ( Abdalla et al, 2019 ). However, there is no coating on MN patches for controlling the cargo leakage, which results in burst release of cargoes at the beginning ( Wang et al, 2020 ).…”
Section: Transdermal Drug Delivery Systemsmentioning
confidence: 99%